2022
DOI: 10.3390/ph15050634
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Short-Term Treatments with Oral Chloroquine and Hydroxychloroquine in Patients with and without COVID-19: A Systematic Review

Abstract: Chloroquine (CQ) and hydroxychloroquine (HCQ) have recently become the focus of global attention as possible treatments for Coronavirus Disease 2019 (COVID-19). The current systematic review aims to assess their safety in short treatments (≤14 days), whether used alone or in combination with other drugs. Following the PRISMA and SWiM recommendations, a search was conducted using four health databases for all relevant English-, Chinese-, and Spanish-language studies from inception through 30 July 2021. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 270 publications
(517 reference statements)
0
7
0
2
Order By: Relevance
“…A systematic review published in April 2021 concluded that the combined odds ratio (OR) of all-cause mortality for the use of HCQ in COVID-19 was 1.11 (95% CI 1.02-1.20) [68]. A systematic review from 2022 additionally found that cardiac adverse events were frequent (0-27.3% and up to 33% if concurrent usage of azithromycin) [69]. Given this overwhelming lack of evidence (despite some of the initial trials) (Table 2), the interest and usage of HCQ/CQ seem to be declining.…”
Section: Summary Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review published in April 2021 concluded that the combined odds ratio (OR) of all-cause mortality for the use of HCQ in COVID-19 was 1.11 (95% CI 1.02-1.20) [68]. A systematic review from 2022 additionally found that cardiac adverse events were frequent (0-27.3% and up to 33% if concurrent usage of azithromycin) [69]. Given this overwhelming lack of evidence (despite some of the initial trials) (Table 2), the interest and usage of HCQ/CQ seem to be declining.…”
Section: Summary Of Researchmentioning
confidence: 99%
“…•, 67•], its usage is not recommended for the treatment of COVID-19. Multiple subsequent large systematic reviews support this recommendation[68,69]. Although, there may be utility for further studies in outpatient COVID-19, or specific sub-groups, at this time, the literature is limited.…”
mentioning
confidence: 99%
“…Первый систематический анализ сообщений случаев кардиотоксичности гидроксихлорохина и хлорохина опубликован уже в сентябре 2020 г. [8] Недавно опубликован новый самый обширный систематический обзор 99 исследований (серии случаев, «случайконтроль», перекрестные, когортные и РКИ) по оценке безопасности гидроксихлорохина и хлорохина при краткосрочном лечении (≤14 дней) COVID-19 при использовании отдельно или в комбинации с другими препаратами [11]. У пациентов с COVID-19 побочные эффекты со стороны сердца, такие как удлинение интервала QT и аритмии, оказались относительно частыми (до 25 и 16,2% соответственно; до 33 и 20,4% в сочетании с азитромицином), но частота развития тахикардии типа «пируэт» низкая (3,4%).…”
Section: гидроксихлорохин и хлорохинunclassified
“…В данный систематический обзор для сравнения характеристики и частоты побочных эффектов гидроксихлорохина и хлорохина включена также группа пациентов с малярией и аутоиммунными воспалительными заболеваниями; сравнение не выявило большую частоту побочных эффектов у пациентов с COVID-19. Однако случаи кардиотоксичности на фоне применения коротких курсов гидроксихлорохина и хлорохина у пациентов с COVID-19 более частые и ранние, что можно объяснить электрофизиологическими эффектами препаратов (блокирование натриевых, кальциевых и калиевых каналов), частой комбинацией с азитромицином и влиянием самого заболевания COVID-19 [11].…”
Section: гидроксихлорохин и хлорохинunclassified
“…Some of these trials raised concerns regarding treatment safety in patients with COVID‐19, particularly cardiovascular adverse events (e.g., conduction disorders), but also dermatological (e.g., hyperpigmentation of the skin), neuromuscular (e.g., weakness), and ophthalmological (e.g., retinopathy) 8 . However, cumulative experience with HCQ showed no increased risk of adverse events in patients with COVID‐19 compared with the use of this drug in approved indications, thus supporting the safe use of this drug 9,10 . Regarding efficacy, trials focusing on hospital‐admitted patients were completed first, consistently demonstrating no clinical effect on the outcome of death 11–13 .…”
Section: Introductionmentioning
confidence: 98%